Strategi Penjualan Produk Olahan Singkong (Sampeuin) di Pandemi Covid-19 di Kabupaten Karawang - Dedi Rianto Rahadi; Hani Tri Lestari; Desita Maharani (Universitas Islam Kadiri, 2022)
Indonesia experienced a drastic economic downturn during the COVID-19 pandemic. The Micro, Small and Medium Enterprises (MSME) sector is the economic sector that is affected. Researchers analyzed from SWOT on the marketing of Sampeuin cassava processed products and determined marketing strategies for Sampeuin cassava processed products in the Covid-19 pandemic. This research was conducted on cassava processing SMEs. In this study, researchers used qualitative research methods. Based on the analysis of the